Dampak Pengungkapan Csr Dan Reputasi Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020 - Riri Mayliza; Nurul Maihidayah (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This study aims to examine the effect of sustainabily report disclosure and company reputation on financial performance. The samples of this present study were companies on the IDX using GRI G4 indicators in dis-closuring sustainability reports in 2016-2020 with the number of research samples as many as 104 companies. The study was quantitative sampling method to collect data. The secondary data were taken from annual reports from CSR and company reputations as influencing factor on financial performance by ROA. This study found that (1) CSR disclosure did not have a significant effect on financial performance and company reputation did not have a significant effect on financial performance.